1989
DOI: 10.1055/s-2006-961994
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic Compounds Isolated from Chinese Cinnamon

Abstract: Two active compounds that prevent serotonin-induced ulcerogenesis in rats were isolated from Chinese cinnamon (the stem bark of Cinnamomum cassia) and identified as 3-(2-hydroxyphenyl)-propanoic acid and its O-glucoside. The former compound, administered orally or parenterally to rats at a remarkably low dose (40 micrograms/kg body weight), also inhibited gastric ulcers induced by the other ulcerogens such as phenylbutazone, ethanol, and water immersion stress, although it failed to prevent indomethacin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 10 publications
1
26
0
2
Order By: Relevance
“…To regain the balance, different therapeutic agents including herbs and spices have been used to inhibit the gastric acid secretion and/or to boost the mucosal defense mechanism by enhancing mucus production (Baggio et al, 2003). The current data clearly demonstrated that cinnamon suspension significantly decreased basal gastric acid secretion and completely inhibited the ulceration in pylorus ligated Shay rats, which concurs with earlier reports of antisecretory and antiulcerogenic actions of two phytoconstituents isolated from Chinese cinnamon (Cinnamon cassia) (Tanaka et al, 1989). In a recent study, Unlu et al (2010) of C. zeylanicum bark.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To regain the balance, different therapeutic agents including herbs and spices have been used to inhibit the gastric acid secretion and/or to boost the mucosal defense mechanism by enhancing mucus production (Baggio et al, 2003). The current data clearly demonstrated that cinnamon suspension significantly decreased basal gastric acid secretion and completely inhibited the ulceration in pylorus ligated Shay rats, which concurs with earlier reports of antisecretory and antiulcerogenic actions of two phytoconstituents isolated from Chinese cinnamon (Cinnamon cassia) (Tanaka et al, 1989). In a recent study, Unlu et al (2010) of C. zeylanicum bark.…”
Section: Discussionsupporting
confidence: 90%
“…However, the volatile oil of cinnamon and its constituents are known to offer protection against gastric damage caused by aggressors in animal models that might be through antioxidant properties (Tanaka et al, 1989). The principal constituents of cinnamon bark are volatile oil, tannins, mucilage, gum, resins, and coumarins.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese cinnamon (Tanaka et al, 1989) have antiulcer activity; licorice (Revers, 1956), Saussuria lappa Clark (Bose et al, 1961;Gupta and Ghatak, 1967), clove (Debelmas and Rochat, 1967) and Asarum sieboldii Miq. (Itokawa et al, 1983) have spasmolytic activity; and licorice possesses gastric secretion inhibitory effect (Hakanson et al, 1973;Takagi and Harada, 1969;Yu, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…PS, 15,16) CB, 17,18) BR, 19,20) MB, 21,22) and JV 23) are reported scientifically proven to have an effect on those clinical condition. Here, these drugs significantly improved BF in stress-enhanced mice (Figs.…”
Section: Modification Of Stress Schedulementioning
confidence: 98%